Exploring Climate Change, Perceptions, and Adaptive Measures among Dairy Producers in Kiruhura District, Uganda - Byamukama, Obed; Agbolosoo, John Atsu (TDMRC, Universitas Syiah Kuala, 2024)
The continuous evidence of climate change highlights the fact that it is a critical worldwide issue with potentially disastrous consequences for agricultural systems and the livelihoods of socioeconomically disadvantaged societies. This research explores dairy producers perceptions of temperature and precipitation changes, their adaptation strategies, and the influencing factors behind these strategies. Data on dairy producers' perceptions was collected by means of a household survey and analyzed utilizing descriptive statistics and graphical representations. Climate data for the study area (19852014) was sourced from the Uganda National Meteorological Authority. It was then analyzed using trend analysis. Results from trend analysis were then used to compare with dairy farmers responses. Notably, the results show significant agreement between dairy farmers' perceptions and empirical climate data, indicating a clear understanding of climate dynamics. This understanding informs their adaptation practices, which have proven to be diverse and context dependent. These practices include the creation of animal pastures, reforestation, reducing the size of herds through sales, utilizing drought-resistant breeds, and purchasing feed additives for livestock. In addition, the study found that access to credit, household size, education level, and gender are important factors affecting pastoralists' adaptability. These results underscore the importance of recognizing and leveraging farmers' experiential knowledge when developing targeted climate adaptation strategies for specific localities. By bridging the gap between perception and reality, this research provides valuable insights for policymakers for developing tailored climate adaptation strategies and improving resilience within dairy-producing communities in response to climate change